DZIELIMY SIĘ DOŚWIADCZENIEMMedical robots in cardiac surgery - Nawrat, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Surgery is a complex procedure requiring precise control of position and force. A review of application of robots in cardiac surgery has been performed. Contemporary history of medical robotics in surgery has been created by the da Vinci and Zeus systems, but the next generation of surgical robots is developing. The Foundation of Cardiac Surgery Development (FCSD) is implementing the project of the Polish robot named Robin Heart and mechatronic tools. The potential applications of robotics in cardiac surgery include: valve replacement and repair, ventricular restraint jacket, transmyocardial laser revascularization, ventricular septal defect, patent ductus arteriosus, and coarctation. The possibility of robot application for heart prostheses implantation and service is considered.